Challenges of CEBAS implementation and maintenance for third sector entities - Júnior, Roberto Reinhardt (2022)
This study aims to present a proposal for pedagogical guidance for the structuring and monitoring of internal accounting control processes for the management of Third Sector (TS) entities, in order to obtain and renew the Certification of Charitable Social Assistance Entities (CEBAS), aiming at maintenance of tax immunity in accordance with Law 12,868/2013. In a descriptive and qualitative approach, using data collection techniques from the following bases: Scientific Electronic Library online, Google Scholar® and Scopus, as well as electronic documents from the Federal Government, legislation and current accounting standards. Adopting the content analysis technique, a pre-analysis was carried out, building the corpus, coding and categorizing the accounting controls. The study is limited to the CEBAS Educação certification, by the criterion of proportion of grant transfers for this segment. The results point to budget control, from enrollment planning, pricing, instruments to control accounts receivable, accounts payable, cash flow, evidencing the entire process of income and expenses, providing the Controller with accounting control tools for adjustments. due between the planned and the realized, preparation of managerial and financial reports. We highlight the documents and accounting statements, thus generating the Entity's legal certainty.